Does captopril interrupt compensatory ovarian changes in hemispayed rats - Chatterjjee, Rita; Jamalullail, Syed Mohsin Sahil; Chatterjee, Amar (1999)
ACE inhibitors are often recommended as the drug of choice to ameliorate essential hypertension. Since the presence of renin-angiotemsin system in the gonadotrophs and the preovulatory fo11ic1e might have a 1ink in ovulatory process, our study has been directed to investigate the possible impact of ACE inhibitor, if any, at the pituitary-ovarian system.Experimental research schedule and the findings as presented in the conference and a1so pub1ished are as follows Strictly 4-day cyclic rats were subjected to surgical hemi-spaying on day 1 of the cycle, distributed into four groups and treated with either captopirl (ACE inhibitor),captorpirl with prolactin, captopirl with progesterone or the vehicle alone. On the following day 1 of the cycle examination of the fallopian tubes and the ovaries of the animals revealed that 70% of the captopril-treated animals fai1ed to ovu1ate but maintained compensatory,ovarian hypertrophy (40.9 + 3.00 Vs 32.4 + 2.6 mg). The remaining 30% of the same group of animals although showed the sign of ovulation and compensatory ovarian enlargement (41.8 + 2.2 Vs 32.4 ± 2.6 mg), yet the number of eggs ovulated were found to be extremely low in count (1.6 + 0.1 Vs 12.3+ 0.4).Conversely, the groups of. animals which had either prolactin or progesterone concurrent with captopirl showed conspensatory changes in terms of ovulation and ovarian hypertrophy as documented in the vehicle-treated controls. While angiotensin helps in the synthesis and re1ease of pro1actin and the progesterone-primed preovu1atory environment of the fo11ic1e is pro1actin dependent, our findings of captopril induced fai1ure of compensatory ovulation in hemispayed rats suggest that angiotensin converting enzyme inhibitor possibly generates a lesion on the prolactin-progesterone system, an essential system to initiate ovulation.